The anti proliferative properties of tinospora crispa on triple negative breast cancer cell lines / Reyadh Radhi Al-Rashidi - Al-Rashidi, Reyadh Radhi (2013)
Tinospora crispa is a traditional medicinal plant in Malaysia with anti-cancer properties as shown in recent studies. The main objective of this study was to determine the antiproliferative effect of T. crispa methanol extract on triple negative breast cancer. MTT assay was performed to determine the cell viability of triple negative breast cancer cell lines (MDA-MB-231 and HCC1806) and normal breast cell line (MCF-10A). The type of cell death was determined using flow cytometry and cellular DNA fragmentation ELISA while Comet assay was used to determine the genotoxicity. qPCR was used to investigate the mRNA expression levels of the caspases 3, 8, 9 and NF-kB. The present results showed that T. crispa decreased the cell viability in triple negative breast cancer cells in a dose dependent manner with an IC50 of 66±3/µg/ml and 60±4µg/ml in MDA-MB-231 and HCC1806 cells respectively. While for MCF-10A, the IC50 was 248±4µg/ml. The type of cell death in MDA-MB-231, HCC1806 and MCF-10A cells was mainly due to apoptosis. The comet assay data for T. crispa did not detect any DNA damage on MDA-MB-231, HCC1806 and MCF-10A cell lines. Our results also showed that cisplatin significantly up-regulated NF-kB gene expression. Many studies reported that the up-regulation of NFkB increases the resistance of cancer cells to apoptosis. Unlike cisplatin, T. crispa did not show any significant change in the mRNA expression levels of NF-kB. Furthermore, when used in combination T. crispa and cisplatin, the combination significantly downregulated the gene expression of NF-kB and significantly up-regulated the gene expression of caspases 3, 8 and 9 in the cancer cells compared to single usage indicating more apoptotic activity. In Conclusion, T. crispa showed anti-proliferative effect on triple negative breast cancer cells with less toxicity to the normal breast cells. The cell death was mainly due to apoptosis and the combination of T. crispa and cisplatin significantly down-regulated the NF-kB gene expression which in turn increased apoptosis in the cancer cell lines.